Water deficit before veraison is crucial in regulating berry VOCs concentration in Sangiovese grapevines - Palai, Giacomo; Caruso, Giovanni; Gucci, Riccardo; D’Onofrio, Claudio (Frontiers in Plant Science, 2023)
The impact of water deficit on volatile organic compounds (VOCs) contributing to grape aroma remains quite unclear. The aim of this study was to evaluate the effect of different timing and intensity of water deficit on berry VOCs and their biosynthetic pathways. Fully-irrigated control vines were compared with: i) two different levels of water deficit from berry pea-size through veraison; ii) water deficit during the lag-phase; iii) two different levels of water deficit from veraison through harvest. At harvest total VOCs concentrations were higher in berries of water stressed vines from berry pea-size through veraison and during the lag-phase, whereas post-veraison water deficit produced similar concentrations as control. This pattern was even more pronounced for the glycosylated fraction and was also observed for single compounds, mainly monoterpenes and C13-norisoprenoids. On the other hand, free VOCs were higher in berries from lag-phase or post-veraison stressed vines. The significant glycosylated and free VOCs increment measured also after the short water stress limited to the lag-phase, highlight the pivotal role played by this stage in berry aroma compounds biosynthesis modulation. The severity of water stress before veraison played a key role as well since glycosylated VOCs showed a positive correlation with the pre-veraison daily water stress integral. The RNA-seq analysis showed a wide regulation induced by irrigation regimes on terpenes and carotenoids biosynthetic pathways. The terpene synthases and glycosyltransferases as well as genes of the network of transcription factors were up-regulated, especially in berries from pre-veraison stressed vines. Since the timing and intensity of water deficit contribute to regulate berry VOCs, irrigation management can be used to achieve high quality grapes while saving water.